Design and development of a stepper motor position control system in micro-stepping mode using Atmega32 Microcontroller - Hasan, Mahmud; Refath, Nehal Hasnain; Ferdus, Rifat (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.